DESAIN MODUL LAPORAN KEUANGAN UNTUK MENINGKATKAN HASIL BELAJAR KOGNISI SISWA KELAS X PERBANKAN SYARIAH DI SMK MUHAMMADIYAH KOTA CIREBON - Iis Hayati; Rochanda Wiradinata; Endang Herawan Endang Herawan (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The research purpose is (1) to arrange or Design learning material of financial statement in a modul. (2) To know implementation process of financial statement module in learning process, and (3) To know improvement of student’s score on accounting subject, especially on financial statement. Subject of this report is accounting class X in SMK Muhammadiyah Cirebon school year 2018/2019 consist of 36 student.Technique of collecting data in this research in unstructured interview, observation, documentation, questionnaire , and test which is analysed by descriptive quantitative and qualitative method. The research result is (1) Designing financial statement module based on research design model 4D that modified into 3D. Define, students need learning materials that can improve their study result. Design, learning materials based on what student needed, it is a financial statement module. Develope, financial statement module that proper with notability average 3,94 through validation by the experts, revise as their criticism and a trial using on X accounting class. (2)Implementation of financial statement module STAD and allocation of 7 lesson hours for three times meeting. (3) Study result are improve significantly based on analysis and wilcoxon trial, average pretest 46,50 and posttest 80,54 with 34,04 improvement, and z= -5,232 sig. 0,000 < 0,05 that showed the improvement of study result between pretest into posttest.